Characterization and formation mechanism of lutein pickering emulsion gels stabilized by β-lactoglobulin-gum arabic composite colloidal nanoparticles. (January 2020) - Su, Jiaqi; Guo, Qing; Chen, Yulu; Dong, Wenxia; Mao, Like; Gao, Yanxiang; Yuan, Fang
Abstract: Composite β-lactoglobulin (β-lg)–gum arabic (GA) particles with superior properties were fabricated as particulate stabilizers for the delivery of lutein. Uniform β-lg-GA particles (β-lgGAPs) with mean particle size of 244.6 ± 2.7 nm and three-phase contact angle (θo/w ) of 90 ± 0.3° were prepared with β-lg to GA mass ratio of 1:2 and pH 4.0. GA molecules were verified to adsorb onto the surface of β-lg nanoparticles, resulting in the formation of β-lgGAPs with a core-shell structure. Afterwards, β-lgGAPs were employed to prepare Pickering emulsions. The formation of creaming was in preference to gelling as determined by diffusing wave spectroscopy and static multiple light scattering. The formed emulsion gels were determined to have a high resistance against flocculation and coalescence as well as remarkable chemical stability: up to 91.1% of lutein was still retained in the emulsion gel containing 70% of oil phase after 12-weeks of storage. Confocal laser scanning microscopy results indicated that the interfacial structure of the oil droplets consisted of both β-lg nanoparticles and GA network, which jointly contributed to the stability of the emulsion gels. These results provide useful information for applications of β-lgGAPs in fabricating lutein emulsion gels via a Pickering mechanism. Graphical abstract: Image 1 Highlights: Food-grade particulate emulsifiers were fabricated through complexation between β-lactoglobulin (β-lg) and gum arabic (GA). Diffusing wave spectroscopy and static multiple light scattering were utilized to monitor the formation of emulsion gels. Both β-lg nanoparticles and GA network jointly contributed to the stability of the emulsion gels. Pickering emulsions stabilized by β-lg–GA particles remained stable during 12-week storage.